Artemvulactone E isolated from Artemisia vulgaris L. ameliorates lipopolysaccharide-induced inflammation in both RAW264.7 and zebrafish model - Zhao, Zibo; Lin, Shimin; Liu, Tao; Hu, Xiao; Qin, Shurong; Zhan, Fengyun; Ma, Jiaqi; Huang, Chen; Huang, Zhibin; Wang, Yifei; Zheng, Kai; Zhang, Wenqing; et al. (Frontiers in Pharmacology, 2024)
Introduction Natural plants are valuable resources for exploring new bioactive compounds. Artemisia vulgaris L. is a traditional Chinese medicinal herb that has been historically used for treating multiple diseases. Active compounds isolated and extracted from A. vulgaris L. typically possess immunomodulatory and anti-inflammatory properties. Artemvulactone E (AE) is a new sesquiterpene lactone isolated and extracted from A. vulgaris L. with unclear biological activities. Methods The immunoregulatory effects of AE on macrophages were assessed by ELISA, RT-qPCR, immunofluorescence, and western blot assay. The effect of AE on lipopolysaccharide (LPS) -relates signaling pathways was examined by western blot assay. In zebrafish models, the larvae were yolk-microinjected with LPS to establish inflammation model and the effect of AE was evaluated by determining the survival rate, heart rate, yolk sac edema size, neutrophils and macrophages infiltration of zebrafish. The interaction between AE and Toll-like receptor 4 (TLR4) was examined by molecular docking and dynamic stimulation. Results AE reduced the expression and secretion of pro-inflammatory cytokines (TNF-α and IL-6), inflammatory mediators iNOS and COX-2, as well as decreases the production of intracellular NO and ROS in LPS-stimulated macrophages. In addition, AE exerted its anti-inflammatory effect synergistically by inhibiting MAPK/JAK/STAT3-NF-κB signaling pathways. Furthermore, AE enhanced the survival rate and attenuated inflammatory response in zebrafish embryos treated with LPS. Finally, the molecular dynamics results indicate that AE forms stable complexes with LPS receptor TLR4 through the Ser127 residue, thus completely impairing the subsequent activation of MAPK-NF-κB signaling. Conclusion AE exhibits notable anti-inflammatory activity and represents as a potential agent for treating inflammation-associated diseases.